Analysis of Labor Absorption in Small and Medium Enterprises in East Java - Mohammad Rizal; Arini Fitria Mustapita (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2024)
Small and medium businesses in East Java as a mainstay sector in labor absorption tend to fluctuate. The problem in this research is how the number of business units, investment and minimum wages correlate with labor absorption in the small and medium enterprise sector in East Java Province. The aim of this research is to analyze the number of business units, investment and minimum wages on labor absorption in the small and medium business sector in East Java Province. The research results obtained by correlation testing the number of SMEs have a significant positive relationship to the labor absorption, investment has a significant positive relationship to the labor absorption and the minimum wage also has a significant positive relationship to the labor absorption. The results of this research indicate that SMEs managers should provide direct credit financing facilities. both bureaucratic and according to the interest rates given, so that government investment which tends to be more capital intensive can be absorbed by SMEs well as well as business training, books and the internet in searching for market information and business management methods so that their businesses can develop more effectively.